The impact of flood control on the loss of wetlands in Argentina - Brandolin, Pablo Germán (2012)
1. Wetlands are among the most important ecosystems on Earth, but historically they have been degraded and destroyed by humans. The south east of Córdoba province in central Argentina was covered by hundreds of wetlands in a vast matrix of grasslands and savannas. In the last few centuries, this area has been mostly transformed into agriculture, forcing wetlands to become the last refuge for remaining wildlife. 2. Since the mid-1970s, a gradual increase in rainfall has enlarged the area occupied by wetlands. To reverse the situation, vast flooded regions were altered by the construction of artificial drainage channels, including important areas for conservation of biodiversity. 3. A non-supervised classification of satellite images was used to assess the changes in flooded areas of south-eastern Córdoba before the main floods (1987?1988) and after channelizations occurred (2007). Areas with high channelization (Córdoba) and non-channelization (Santa Fe) were compared for years with the same amount of accumulated rainfall. 4. The pluviometric registers in both regions showed a trend of increasing annual rainfall, and this was reflected in a 65.9% increase (64 837 ha) of the flooded area in Santa Fe. Conversely, the channelized area in Córdoba suffered a loss of 12% of its ponds, corresponding to a 14.7% reduction of the flooded area (11 655 ha). A greater reduction in the flooded area (42.1%) was observed when considering only the western portion of the Córdoba site where most of the channelization occurred. 5. These results indicate that besides the mitigation of floods, the channelization in Córdoba favoured agriculture expansion at the expense of wetlands, thereby destroying these wildlife refuges. Wetlands are important for their biodiversity, ecosystem services, and cultural legacy. In central Argentina the channelization process still continues, so it is of the utmost importance to support conservation actions leading to sustainable management and territorial planning of this region.